The Effects of Victimization on Offending: An Examination of General Strain Theory, Criminal Propensity, Risk, Protection, and Resilience - Kushner, Mackenzie (Victims & offenders, 2023)
General strain theory (GST) proposes that criminal coping is most likely for victims who possess multiple individual and environmental risk factors that together create a strong propensity for offending. However, this conceptualization does not consider the potential buffering effects of multiple protective factors on the victimization/offending relationship. This study addresses this limitation using self-report data from waves I and II of the National Longitudinal Study of Adolescent to Adult Health (Add Health) (N = 13,346). Negative binomial logistic regression models assessed the conditioning effects of composite and individual measures representing criminal propensity/risk and protection/resilience on the victim/offending relationship. Results support GST’s premise that victimization increases involvement in offending but, contrary to GST, greater risk weakened the relationship between victimization and offending while greater protection strengthened this relationship. Findings highlight a need for further theoretical development and a greater understanding of the subjective experience of victimization and pathways associated with increased risk and resiliency.